2021
DOI: 10.16984/saufenbilder.742432
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Phenolic Compounds, Organic Volatile Molecules and Anti-Cancer Properties in Inula Viscosa L., Viscum Album L. and Raphanus Sativus L.

Abstract: The plants elecampane (Inula Viscosa L.), mistel (Viscum album L.) and black radish seed (Raphanus Sativus L.) have been used in the treatment of common diseases worldwide as part of traditional medicine for many years. Especially in Turkey, elecampane plant is commonly used as remedy of cancer. In this study, phytochemical components of these three plants were analyzed using liquid chromatography-mass spectrometer/mass spectrometer and gas chromatography-mass spectrometer techniques. Antioxidant activity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
(57 reference statements)
0
5
0
Order By: Relevance
“… 97 The current cancer treatments have many side effects and tumors started developing resistance to them. 98 Therefore, finding new innovative treatment that are less aggressive and more efficient becomes a necessity. Many researchers focused on investigating plants as a natural source of various bioactive compounds that showed promising results in combating different cancers while reducing the side effect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 97 The current cancer treatments have many side effects and tumors started developing resistance to them. 98 Therefore, finding new innovative treatment that are less aggressive and more efficient becomes a necessity. Many researchers focused on investigating plants as a natural source of various bioactive compounds that showed promising results in combating different cancers while reducing the side effect.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers focused on investigating plants as a natural source of various bioactive compounds that showed promising results in combating different cancers while reducing the side effect. 98 D. viscosa has been widely investigated for its antineoplastic effects on various cancers. Table 11 summarizes the key findings reported in the literature on the anticancer activity of D. viscosa .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LC‐ESI‐MS/MS based qualitative characterization of 37 phytochemicals (including flavonoids and phenolic acids) was selected based on the diversity of the flavonoids and phenolic acids found in the aqueous pollen grain extracts with relatively larger quantities. The details of the protocol can be found elsewhere [61] …”
Section: Methodsmentioning
confidence: 99%
“…The clinical trials reported immunoadjuvant, antioxidant, and anti-inflammatory properties [ 37 ], including the utilization of the extracts to improve the quality of life of the treated subjects [ 38 ]. In this scenario, the antioxidant activity plays a central role, together with the anti-inflammatory properties [ 39 , 40 , 41 , 42 ]. The most reported active constituents are known flavonoids, which are present in alcoholic and aqueous extracts [ 43 , 44 ] and are already reported for their anti-ROS and radical-scavengers properties [ 45 ], with attention to the variation of the phenolic content in relation to the host [ 46 , 47 ] and the investigated subspecies [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: The European Mistletoementioning
confidence: 99%